Software Project Management Malaysian Companies. - Lye On, Dino Ang (2007)
This paper will take to identify the software management process and how this can affect the quality of the software. In addition, a survey was conducted to analyze whether worker\'s skill also affect the entire software management process. Also, there are dicussion about post implementation approaches adopted by software companies in Malaysia and whether the software processes have been provided tender care it needs to survive in changing environmentit is found to be in.